Extensive Evaluation via Blinded Testing of an UHPLC-MS/MS Method for Quantitation of Ten Ergot Alkaloids in Rye and Wheat Grains. (4th January 2021) - Tkachenko, Andriy; Benson, Kelly; Mostrom, Michelle; Guag, Jake; Reimschuessel, Renate; Webb, Brett
Abstract: Background: Ergot alkaloids are mycotoxins produced by the fungus Claviceps, which can contaminate grains and pose a health risk to humans and animals. Validation of an ergot alkaloid method in collaborative projects can be challenging due to instability of analytes, a lack of reliable reference materials, and a fully validated reference method. Objective: To extensively evaluate performance of a quantitative UHPLC–MS/MS method to detect ten ergot alkaloids at concentrations between 16 and 500 ng/g in grains. Method: The method performance was evaluated in the Blinded Method Test (BMT) exercise, which allowed organizers to successfully address the challenges. Forty completely blinded test samples were prepared in an independent laboratory and shipped to a participating laboratory to analyze on two separate days. Results: Precision, accuracy, and HorRatr values met or exceeded the U.S. Food and Drug Administration recommendations. The design of the BMT exercise provided a high degree of confidence in data and conclusions drawn. Conclusions: The method performed in a manner as expected, and the method can be used by the laboratory for routine testing of wheat and rye grains. Highlights: BMT of laboratory methods facilitate validation of tests by evaluating performance in an unbiased manner.